Level of pain and satisfaction with pain management after lower segment caesarean section among Malaysian women in two public hospitals - N.Govindasamy, Thanageswary (2019)
As compared to the vaginal delivery, the Lower Segment Caesarean Section (LSCS) operation is easier to perform but women who undergo LSCS experience a higher level of pain. Study done by the Institute for Public Health 2008, the Ministry of Health Malaysia reported that pain rating was greater among Indian women (28.4%) compared to Chinese (9.9%) and Malay (8.2%) women. It is important to provide adequate pain relief as early mobilization to prevent the risk of thromboembolic disease, which increases during pregnancy. Mothers need to be pain-free to care for their new-borns and breastfeed them effectively. Thus, this study aims to determine the level of pain and satisfaction with pain management after LSCS among Malaysian women in two public hospitals. This study employed a structured survey using interview to collect data from chosen respondents. Samples studies were selected from its population using cluster sampling technique. The respondents were 126 post LSCS mothers. The questionnaire consists, of 18 questions and divided into three main sections. Data were analysed using SPSS version 22. Level of pain was reported within and 24 hours after LSCS, showing that all respondents majority of them experiencing moderate level of pain. There was no statistically significant association (p-value=0.056) found between ethnicity and pain level within 24 hours after LSCS. However, there existed an association between different ethnicities and pain level after 24 hours of LSCS operation (p-value 0.002). Where as severe pain was approximately equally distributed (40%) for both Chinese and Indian women. The results of this study showed after pain management on types of analgesia had a statistically significant different management in hospitals, HSA and HSI, and overall dissatisfaction.